Identification of Bacteria in Fresh Vegetables from The Traditional Market of Mataram City - Syamsul Bahri; Rika Ratnasari; Ulfah Nurkhaeroni; Mujitahid Mujitahid (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Indonesia is very rich in potential for vegetable cultivation. Vegetables contain a lot of vitamins and minerals. Therefore, people prefer to eat vegetables in a fresh state either as salads or fresh vegetables. However, contamination of pathogenic bacteria is much greater both at the farmer and trader levels. Therefore this study aims to determine the feasibility of consumption and identify bacteria in fresh vegetables in the traditional market of Mataram City. Samples in the form of lettuce, cucumber, cabbage, and long beans were taken from Pagesangan, Kebon Roek, Gunung Sari, and Bertais markets, respectively. The existence of bacteria were detected using traditional method by inoculating samples in agar cultures followed by biochemical testing and Gram staining. Species of bacteria that can be identified from samples are Enterobacter cloacae, Bhanhamella catarrhalis, E-coli, Staphylococus sapropyticus, and Aeromonas hydrophila. Based on the data, long beans from the Bertais market and lettuce from the Pagesangan, Kebon Roek, and Gunung Sari markets are not suitable for consumption because the TPC yield exceeds the consumption quality standard of 105-106 CFU/g.